PELATIHAN PENULISAN CERPEN REMAJA PADA SISWA SMP NEGERI 8 KOTA TANGERANG SELATAN - Adam Muhammad Nur; Yasir Mubarok; Washadi Washadi; Eris Risnawati (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2020)
The literacy culture of literary works today needs to be encouraged. Considering several government programs that insert some literacy-related teaching were developed and carried out in schools. Like some literacy movements pursued by the Ministry of Education and Culture in schools to improve children's reading ability, especially at the junior and senior high schools. But it should also be noted that literacy culture is not only focused on reading but also present in other forms of language activities namely writing. It cannot be denied that the art of writing is very important. Not only to write ideas into writing but also by writing, the information that we want to convey can spread well especially in this digital era, an article now will be very easily published even posted through social media accounts or other digital media. In order for children or especially students to write well and develop their ideas, the PKM team from the Faculty of Literature, Indonesian Literature Study Program held a dedication to the community to foster a literacy culture in the field of writing. The training that was held by the PKM team was a training on writing short stories with the theme of teenagers who are very close to children, especially junior high school students. The activity that took place at the South Tangerang 8 Middle School is expected to help children become more creative and can help them develop their writing skills.